A new record of Rhizoctonia butinii associated with Picea glauca 'Conica' in Slovenia. Issue 3 (9th March 2016) - Hauptman, T.; Piškur, B.
Summary: In 2013, the death of needles of dwarf Alberta spruce ( Picea glauca 'Conica') seedlings was observed in an arboretum in Slovenia. Needles on infected P. glauca 'Conica' twigs were covered with thick, yellowish brown hyphal cushions. The outgrowing mycelium was white and had completely overgrown some needles and connected them to each other. To definitively identify the fungus affecting P. glauca 'Conica', morphological examinations of isolated pure cultures were performed, and the internal transcribed spacer (ITS) region of the rDNA was sequenced. Based on morphological and molecular phylogenetic analyses together with the performed pathogenicity trial, we identified the causal agent of the observed symptoms as Rhizoctonia butinii – a recently described species. This report connects this fungus to a new locality and a new host plant.